2017
DOI: 10.1249/mss.0000000000001180
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sedentary Time, and Fatness in a Biethnic Sample of Young Children

Abstract: Purpose-To investigate associations of objectively-measured physical activity (PA) and sedentary time (ST) with adiposity in a predominantly bi-ethnic (South Asian and White British) sample of young children.Methods-The sample included 333 children aged 11 months to 5 years who provided 526 crosssectional observations for PA and body composition. Total PA volume (vector magnitude counts per minute (cpm)), daily time at multiple intensity levels (the cumulative time in activity >500 cpm, >1000 cpm, >1500 cpm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 36 publications
2
54
1
Order By: Relevance
“…Offspring PA at 2 years tended to be negatively correlated with their adiposity ( P = 0.08). This is in agreement with a study by Collings et al that showed an inverse association between PA and adiposity in children 11 months to 5 years of age. These findings emphasize the importance of PA beginning in early childhood to possibly reverse or mitigate adverse adiposity accrual that occurs in early infancy.…”
Section: Discussionsupporting
confidence: 94%
“…Offspring PA at 2 years tended to be negatively correlated with their adiposity ( P = 0.08). This is in agreement with a study by Collings et al that showed an inverse association between PA and adiposity in children 11 months to 5 years of age. These findings emphasize the importance of PA beginning in early childhood to possibly reverse or mitigate adverse adiposity accrual that occurs in early infancy.…”
Section: Discussionsupporting
confidence: 94%
“…Data were pooled from three projects that are related to the Born in Bradford birth cohort study [14] and research programme (www.borninbradford.nhs.uk). Two projects were observational studies [15,16] and another was a multiple time-point school-based pilot cluster randomised control trial (RCT) that targeted preschool children [17]. Each study included objective measurement of free-living physical activity in young children living in Bradford, which is one of most deprived and ethnically diverse cities in the UK [18].…”
Section: Methodsmentioning
confidence: 99%
“…Skinfolds of the left triceps and subscapular were measured to the nearest 0.1 mm and were combined to their total sum. Reliability metrics indicated good intra-and interobserver technical error for measurements (5).…”
Section: Adiposity Measurementsmentioning
confidence: 95%